Polycystic ovary syndrome: Risk factors and prevention - Sununta Youngwanichsetha (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Polycystic Ovary Syndrome (PCOS) is a common reproductive health problem among women worldwide. It is associated with androgen excess, anovulation, abnormal menstruation, and sub-infertility. Other manifestations of PCOS are acne, abnormal hair growth, alopecia, and male-pattern baldness.